Negative and positive externalities in intergroup conflict: exposure to the opportunity to help the outgroup reduces the inclination to harm it - Weisel, Ori (Frontiers in Psychology, 2015)
Outgroup hate, in the context of intergroup conflict, can be expressed by harming the outgroup, but also by denying it help. Previous work established that this distinction---whether the externality on the outgroup is negative or positive---has an important effect on the likelihood of outgroup hate emerging as a motivation for individual participation in intergroup conflict. The current work uses a within-subject design to examine the behaviour of the same individuals in intergroup conflict with negative and positive externalities on the outgroup. Each participant made two choices, one for each type of externality, and the order was counter balanced. The main results are that (1) behaviour is fairly consistent across negative and positive externalities, i.e., the tendency to display outgroup hate by harming the outgroup is correlated with the tendency to display outgroup hate by avoiding to help the outgroup; (2) People are reluctant to harm the outgroup after being exposed to the opportunity to help it; (3) Groupness---the degree to which people care about their group and its well-being---is related to outgroup hate only when participants encounter the opportunity to harm the outgroup first (before they encounter the opportunity to help it). In this setting the relationship between groupness and outgroup hate spilled over to the subsequent interaction, where it was possible to help the outgroup. When the opportunity to help the outgroup was encountered first, groupness was not related to outgroup hate.